The Effectiveness of Gamification With Kahoot on English Language Vocabulary Mastery - Murtasiah, Murtasiah; Riswanto, Riswanto; Haryanto, Endang (The Future of Education Journal, 2025)
Vocabulary is one of the fundamental aspects of English learning and plays a crucial role in supporting students’ ability to communicate effectively. However, many students still face challenges in mastering vocabulary, especially when learning relies only on conventional methods. Gamification, such as the use of Kahoot, provides an alternative strategy that combines learning with interactive and engaging activities. This study aimed to investigate the effectiveness of gamification with Kahoot on the vocabulary mastery of sixth-grade students at SDN 06 Sungai Rumbai. A quantitative approach was applied using a one-group pretest-posttest design with 29 participants. The treatment was conducted through interactive classroom sessions where students practiced vocabulary using Kahoot games. The research instrument consisted of 50 multiple-choice items, of which 24 were validated and used in the pretest and posttest. Results showed an increase in average scores from the pretest to the posttest, with a significance value of less than 0.05, indicating a significant effect. It can be concluded that the use of Kahoot as a gamified learning platform effectively improves students’ vocabulary mastery and can serve as an innovative medium in English language teaching, particularly for young learners.